Subnational Inequality in Latin America: Empirical and Theoretical Implications of Moving beyond Interpersonal Inequality (2019)
In many countries around the world, living in one subnational unit versus another can be just as important as race or class as a determinant of differential access to opportunities and wellbeing. Despite this fact, scholars still heavily emphasize interpersonal income inequality. This article develops and implements new tools to shift from interpersonal to subnational inequality and from economic to social inequality. It develops a novel concept and measurement of subnational social inequality that overcomes the inconsistencies between definitions and measurements found in existing research on the subject. Focusing on Latin America, the article applies the new measurement tools to reveal differences in the evolution and rankings of interpersonal and subnational forms of inequality. Such findings challenge our existing knowledge of both the levels and the sources of inequality in the region. To make sense of these discoveries, the article suggests that the usual drivers of interpersonal inequality—such as neoliberal reforms and authoritarianism—might drive down subnational inequality, while well-known inequality fighters—such as democratization and left party rule—might not be as effective at combating its subnational variety. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.